Malay Arts and Crafts - Sheppard, Mubin, 1905-1994 (Book collections on Project MUSE., 2011)
Much has been written about Malaya's history but relatively little about its arts and crafts. Malay Arts and Crafts, is a detailed study of Malay arts, crafts and culture.